Genetically modified chickens as bioreactors for protein-based drugs - Meng, Shujuan; Miao, Aijun; Wu, Sen; Du, Xuguang; Gao, Fei (Frontiers in Genome Editing, 2025)
Protein drug production encompasses various methods, among which animal bioreactors are emerging as a transgenic system. Animal bioreactors have the potential to reduce production costs and increase efficiency, thereby producing recombinant proteins that are crucial for therapeutic applications. Various species, including goats, cattle, rabbits, and poultry, have been genetically engineered to serve as bioreactors. This review delves into the analysis and comparison of different expression systems for protein drug production, highlighting the advantages and limitations of microbial, yeast, plant cell, and mammalian cell expression systems. Additionally, the emerging significance of genetically modified chickens as a potential bioreactor system for producing protein-based drugs is highlighted. The avian bioreactor enables the expression of target genes in ovarian cells, resulting in the production of corresponding gene expression products in egg whites. This production method boasts advantages such as a short cycle, high production efficiency, low research costs, and the expression products being closer to their natural state and easier to purify. It demonstrates immense potential in production applications, scientific research, and sustainable development. The utilization of advanced gene editing technologies, such as CRISPR/Cas9, has revolutionized the precision and efficiency of generating genetically modified chickens. This has paved the way for enhanced production of recombinant therapeutic proteins with desired glycosylation patterns and reduced immunogenic responses.